1999
DOI: 10.1097/00000542-199902000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic Prophylaxis Does Not Improve Outcomes after Outpatient Surgery When Compared to Symptomatic Treatment 

Abstract: Although PONV is unpleasant, the data indicate little difference in outcomes when routine prophylactic medications are administered versus simply treating PONV should symptoms occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(79 citation statements)
references
References 17 publications
2
72
0
5
Order By: Relevance
“…This finding is supported by other authors 16 . Discussion is still on-going about whether intervention for PONV should take place preoperatively or if symptoms should be treated 17 . Systematic reviews suggest that prophylaxis is not always successful.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by other authors 16 . Discussion is still on-going about whether intervention for PONV should take place preoperatively or if symptoms should be treated 17 . Systematic reviews suggest that prophylaxis is not always successful.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who develop PONV despite receiving prophylaxis, an antiemetic acting at a different receptor should be used for rescue within the first six hours following surgery. 144 After six hours, PONV can be treated with any of the drugs used for prophylaxis except dexamethasone and scopolamine.…”
Section: Combination Antiemetic Therapy and Multimodal Approachmentioning
confidence: 99%
“…No major benefit for routine antiemetic prophylaxis has been shown when drugs are administered non-selectively. 6 Such results are not without contradiction and Sadhasivam et al 9,10 reported that routine prophylaxis with ondansetron not only decreased the incidence and frequency of PONV but also led to greater patient satisfaction. The main reason for these inconsistencies may be related to differences in the underlying patient risk for PONV.…”
Section: Prophylaxis or Treatment Of Ponv?mentioning
confidence: 99%
“…A clinically significant improvement in patient satisfaction with prophylaxis seems to occur mainly in subgroups of patients at a high risk for PONV. 6,11 Therefore, a cost-effective approach to the management of PONV would be to provide prophylactic antiemetic therapy in situations with a high-risk of emesis and to give treatment for established PONV in situations where the risk is lower. In order to make such decisions for PONV management, it is mandatory to know the incidence of PONV in the local setting (e.g., by using an established risk score to assess the risk for PONV).…”
Section: Prophylaxis or Treatment Of Ponv?mentioning
confidence: 99%
See 1 more Smart Citation